2014
DOI: 10.1159/000362398
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy Is Effective for Desmoid Tumors (Aggressive Fibromatosis) - Long-Term Results of a German Multicenter Study

Abstract: Background: Desmoids (aggressive fibromatosis) are defined as benign neoplasms of the connective tissue that arise from the deep muscle fascia, aponeurosis, tendons, and scar tissue. Recurrence rates between 40 and 80% were reported after surgery alone. We addressed the impact of radiation therapy (RT) in the management of aggressive fibromatosis. Patients and Methods: A large literature review was performed, and the data was compared with the results of a multicenter study of the German Cooperative Group on R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Sufficient data for analysis were published in two articles; authors from the other 50 articles were contacted and requested to provide the additional data needed. Of these, 14 responded, bringing the total number of included studies to 16 ( Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient data for analysis were published in two articles; authors from the other 50 articles were contacted and requested to provide the additional data needed. Of these, 14 responded, bringing the total number of included studies to 16 ( Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Baumert et al 36 Bertani et al 37 Bonvalot et al 11 Cates and Stricker 24 Eastley et al 38 Gronchi et al 22 Huang et al 39 Ihalainen et al 40 Kriz et al 41 Pignatti et al 42 Prodinger et al 43 Salas et al 25 Stoeckle et al 44 van Broekhoven et al 23 Wang et al 45 Wilkinson et al 46 Total Heterogeneity: 37 Bonvalot et al 11 Cates and Stricker 24 Eastley et al 38 Gronchi et al 22 Huang et al 39 Ihalainen et al 40 Kriz et al 41 Pignatti et al 42 Prodinger et al 43 Salas et al 25 Stoeckle et al 44 van Broekhoven et al 23 Wang et al 45 Wilkinson et al 46 Total Heterogeneity: χ 2 = 7·97, 3 d.f., P = 0·05; I 2 = 62% Test for overall effect: Z = 2·50, P = 0·01 Bertani et al 37 Bonvalot et al 11 Cates and Stricker 24 Eastley et al 38 Gronchi et al 22 Huang et al 39 Ihalainen et al 40 Kriz et al 41 Pignatti et al 42 Prodinger et al 43 Salas et al 25 Stoeckle et al 44 van Broekhoven et al 23 Wang et al…”
Section: Role Of Adjuvant Radiotherapymentioning
confidence: 99%
“…Patients who are not surgical candidates or who refuse surgery are indicated for radiation therapy alone, and several studies have shown that radiation therapy alone results in durable local control rates of 70-80%. 2,[13][14][15] However, studies on radiotherapy have focused on extra-abdominal aggressive fibromatosis, and most of the tumour sizes are significantly ,10 cm; therefore, the median total dose of 56 Gy has a better therapeutic effect on local control. In this study, all of the tumours were diagnosed as intra-abdominal aggressive fibromatosis with sizes .10 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Woltsche et al (13) and Soto-Miranda et al (14) found the condition of the resection margin does not impact the local control rate of surgery, which indicated that DT has unique biological behavior, challenges the effectiveness of radical resection and highlights the need of adjuvant therapy like chemotherapy.…”
Section: Surgerymentioning
confidence: 99%